2015
DOI: 10.1016/j.jssc.2015.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Combined experimental and theoretical assessments of the lattice dynamics and optoelectronics of TaON and Ta3N5

Abstract: a b s t r a c tPresented herein is a detailed discussion of the properties of the lattice dynamic and optoelectronic properties of tantalum(V) oxynitride (TaON) and tantalum(V) nitride (Ta 3 N 5 ), from experimental and theoretical standpoint. The active Raman and infra red (IR) frequencies of TaON and Ta 3 N 5 were measured using confocal Raman and Fourier Transform Infrared spectroscopies (FTIR) and calculated using the linear response method within the density functional perturbation theory (DFPT). The deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 62 publications
19
76
0
Order By: Relevance
“…34,35 we computed the infrared and Raman frequencies of Ta 3 N 5 at the Brillouin Zone center (see Table SI) using PBE, and we found excellent agreement with the theoretical and experimental data of Ref. 36. We also found that frequencies larger than 300 cm −1 are dominated by N displacements.…”
Section: Resultssupporting
confidence: 78%
“…34,35 we computed the infrared and Raman frequencies of Ta 3 N 5 at the Brillouin Zone center (see Table SI) using PBE, and we found excellent agreement with the theoretical and experimental data of Ref. 36. We also found that frequencies larger than 300 cm −1 are dominated by N displacements.…”
Section: Resultssupporting
confidence: 78%
“…The frequencies of 140.7, 401.8, 523.3, and 898.1 cm −1 can be assigned to Ag modes and 125, 178.6, 238.8, 265.6, 492.9, 599.1, and 746.6 cm −1 correspond to Bg modes. [15] All peaks are consistent with the theoretical calculations with an error value less than 5 cm −1 , indicating that these nanomeshes are single-phase Ta 3 N 5 . X-ray photoelectron spectroscopy (XPS) was used to examine the chemical states of Ta and N in the Ta 3 N 5 nanomeshes (Figure 3c,d).…”
supporting
confidence: 84%
“…A laser of 337 nm was used as excitation source and the lifetime of photons at the wavelength of 586 nm (2.116 eV) was monitored due to the highest emission intensity of Ta 3 N 5 under this wavelength. [15] As shown in Figure 5c, the fluorescent intensities decay exponentially for both samples. Noticeably, the nanomesh shows slow decay kinetics compared to the bulk.…”
mentioning
confidence: 71%
“…Because there is only limited literature describing the Raman modes of Ta 3 N 5 , a detailed assignment for Ta 3 N 5 Raman modes based on theoretical calculations was previously performed in our recent study. 21,56 To summarize, the theory predicted for the orthorhombic allotrope (Cmcm) of Ta 3 N 5 a total of 24 Raman-active modes (8A g +16B g ). X-ray absorption spectroscopy (XAS) with sensitive fluorescence detection was used to unveil the local environment of the cobalt.…”
Section: Chemistry Of Materialsmentioning
confidence: 98%